PENERAPAN PRINSIP-PRINSIP EVALUASI DALAM MATA PELAJARANPENDIDIKAN AGAMA ISLAM (PAI) - Usman DP (STKIP Paris Barantai, 2020)
Islamic religious education becomes a cluster of subject group that is an integral part of the scope of the principles and objectives of evaluation activities. PAI subject are a component of the Islamic education system which is recognized for existence in our national educational system. Therefore, PAI as a subject must be evaluated systematically and planed. Applying proper and coreect evaluation principles and prosedure can improve the performance, productivity, and quality of the teachers and educational institutions in a effort to respond to various challenges facing islamic education to day are so complex and increasingly complicated. For that, reliable and accurate evaluation system based on data and facts is needed. From these data and facts, its becomes infromation material in taking improvements and improving the quality of education and teaching and in taking decesions. Thywords: Application, Principles, and PAI Subject.